گاما رو نصب کن!

{{ number }}
اعلان ها
اعلان جدیدی وجود ندارد!
کاربر جدید

جستجو

پربازدیدها: #{{ tag.title }}

میتونی لایو بذاری!

اگر $f(x) = (x - 4)\sqrt[3]{{x + 3}}$ باشد، حاصل $\mathop {\lim }\limits_{h \to 0} \frac{{{f^2}(5 - h) - 3f(5 - h) + 2}}{{h(5 - h)}}$ کدام است؟

1 ) 

$\frac{{13}}{{30}}$

2 ) 

$ - \frac{5}{{12}}$

3 ) 

$\frac{{5}}{{6}}$

4 ) 

$ - \frac{13}{{15}}$

پاسخ تشریحی :
نمایش پاسخ

$ = \mathop {\lim }\limits_{h \to 0} \frac{{f(5 - h) - 2}}{h} \times \frac{{f(5 - h) - 1}}{{5 - h}} = \mathop {\lim }\limits_{h \to 0} \frac{{f(5 - h) - f(5)}}{h} \times \frac{{2 - 1}}{5} = \frac{{ - 1}}{5}f'(5)$

$f'(x) = \sqrt[3]{{x + 3}} + (x - 4)\frac{1}{{3\sqrt[3]{{{{(x + 3)}^2}}}}} \to f'(5) = 2 + \frac{1}{{12}} = \frac{{25}}{{12}}$

$ \to \frac{{ - 1}}{5}f'(5) = \frac{{ - 5}}{{12}}$

تحلیل ویدئویی تست